Proyecto de inversión para el posicionamiento de la cabaña del alemán en el mercado de la ciudad de la libertad - Floreano Tumbaco, Washington Oswaldo (2009)
The reason why there is need for this project is that the Santa Elena Peninsula there is a place of entertainment with different customs, in which the inhabitants of that part of the country are familiar. A place where you can enjoy a varied cuisine, which also can learn more about customs of other countries. The project applied everything we need people in the peninsula of Santa Elena, as it provided an excellent German cuisine with the best drinks in that country, a good atmosphere and an attention to the first users become accustomed to this new concept of location. "The cabin of the German" will benefit the tourism peninsular, as the opening of this location will attract not only the expectations of the peninsular, but the rest of the country, and why not people from other countries. This will increase not only our customers but also impact on local tourism; the local will be located in the Malecon of La Libertad. This will change the concept of having the mainland as a family how to have fun, because the local environment of the decorations consist of family members, besides an excellent attention to motivate people to visit the local wish to return.